DEVELOPMENT AND TRANSLATION FEATURES OF AN AVIATION TERMINAL SYSTEM FROM ENGLISH TO RUSSIAN (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The article explores both general and specific aspects concerning the establishment of an aviation terminology system and the primary methods used for translating these terms from English into Russian. It emphasizes various processes involved in term formation, influencing their emergence and usage in today's linguistic context. By examining industry-specific English and Russian aviation terminologies, the study identifies certain underlying patterns. The analysis underscores that the inclusion of terms within specialized vocabularies signifies shared processes in word and phrase formation across contemporary English and Russian languages.